Desmopressin after cardiac surgery in bleeding patients. A multicenter randomized trial. Issue 7 (27th April 2016) - Bignami, E.; Cattaneo, M.; Crescenzi, G.; Ranucci, M.; Guarracino, F.; Cariello, C.; Baldassarri, R.; Isgrò, G.; Baryshnikova, E.; Fano, G.; Franco, A.; Gerli, C.; et al.
Abstract : Background: Previous studies showed that desmopressin decreases post‐operative blood loss in patients undergoing cardiac surgery. These studies were small and never studied the effect of desmopressin in patients with active bleeding. Objective of the study was to determine whether desmopressin reduces red blood cells transfusion requirements in patients with active bleeding after cardiac surgery who had been pre‐treated with tranexamic acid. Methods: This multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group study randomized elective patients with bleeding after cardiac surgery despite pre‐treatment with tranexamic acid, to receive placebo (saline solution) or a single administration of desmopressin (0.3 μg/kg in saline solution). The primary endpoint was the number of patients requiring red blood cells transfusion after randomization and during hospital stay. Secondary end points were: blood loss from chest tubes during the first 24 h after study drug administration, hours of mechanical ventilation, intensive care unit stay, and in‐hospital mortality. Results: The study was interrupted after inclusion of 67% of the planned patients for futility. The number of patients requiring red blood cells transfusion after randomization was 37/68 (54%) in desmopressin group and 33/67 (49%) in placebo group ( P = 0.34) with no difference in blood loss: 575 (interquartile 422–770) ml in desmopressin group and 590 (476–1013) ml in placebo group ( P = 0.42), mechanical ventilation, intensive care unit stay or mortality. Conclusions: This multicenter randomized trial demonstrated that, in patients pre‐treated with tranexamic acid, desmopressin should not be expected to improve treatment of patients who experience bleeding after cardiac surgery.